The effect of Psidium guajava Leaves' extract for mild and asymptomatic corona virus Disease-19 - Fredia Heppy; Roza Mulyana; Nur Afrainin Syah; Raymond R. Tjandrawinata (Elsevier, 2023)
COVID-19 is an emerging disease that attacks the respiratory and systemic systems. Various treatments have been used for COVID-19, but no antiviral agents seemed to be efficacious. Many medicinal plants are commonly used for viral infections in Indonesia, including the guajava leaf. The study aimed to determine the effects of Psidium guajava extract supplementation on inflammation markers of asymptomatic and mild COVID-19 patients. The conversion time of PCR results was also evaluated. This study was an experimental, single-blinded, randomized clinical trial (ClinicalTrials.gov: NCT04810728) comparing the efficacy of P. guajava extract at the dose of 1000 mg/8h on top of standard treatment with the standard treatment only for asymptomatic and mild COVID-19 subjects. The primary endpoints were neutrophil and lymphocyte percentages as well as the neutrophil/lymphocyte ratio (NLR) on day 7 of the treatment. The secondary endpoints were high-sensitivity c-reactive protein (hs-CRP) level, PCR-based conversion time, and recovery rate at weeks 2 and 4. A total of 90 subjects were enrolled, and there were 40 subjects in the P. guajava (experimental) group and 41 subjects in the control group who completed the research. On day 7, significantly lower percentage of neutrophil (52.4% vs 58.9%, p = 0.002), higher lymphocyte percentage (35.5%, vs 29.7%, p = 0.002), and lower NLR (1.5 vs 2.1, p = 0.001) were demonstrated in the experimental versus control group. The PCR-based conversion time was shorter (14 days vs 16 days, p < 0.001), and recovery rate at 2 and 4 weeks were higher (49% vs 27%, p = 0.03 and 100% vs 82%, p = 0.003, respectively) in the experimental group. There were no differences in the baseline characteristics. P. guajava extract supplementation reduced neutrophil and increased lymphocyte percentages which led to reduced NLR, accelerated PCR-based conversion time, and increased recovery rate in subjects with mild and asymptomatic COVID-19 infection.